2015
DOI: 10.1021/acs.orglett.5b01832
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Normorphans through an Efficient Intramolecular Carbamoylation of Ketones

Abstract: An unexpected C-C bond cleavage was observed in trichloroacetamide-tethered ketones under amine treatment and exploited to develop a new synthesis of normophans from 4-amidocyclohexanones. The reaction involves an unprecedented intramolecular haloform-type reaction of trichloroacetamides promoted by enamines (generated in situ from ketones) as counter-reagents. The methodology was applied to the synthesis of compounds embodying the 6-azabicyclo[3.2.1]octane framework.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…It has been observed that the 2-amino-1,3,4-thiadiazole moiety may be a good group for anti-HIV-1 activity by providing promising antiviral agents. (7) substitution with F atoms (8,9) X = N heterocyclic ring increases activity introduction of CH 3 Although they exhibited less anti-HIV-1 activity compared to standard drug zidovudine (half-maximal inhibitory concentration IC 50 = 0.016 µM), these compounds showed significant anti-HIV-1 activity at micromolar concentrations (IC 50 within the range of 7.50-20.83 µM) ( Table 1). The introduction of electron-withdrawing groups, such as fluorine or trifluoromethyl on phenyl ring (derivatives 8 and 9), enhanced antiviral activity compared to the unsubstituted phenyl derivative 7.…”
Section: -10mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been observed that the 2-amino-1,3,4-thiadiazole moiety may be a good group for anti-HIV-1 activity by providing promising antiviral agents. (7) substitution with F atoms (8,9) X = N heterocyclic ring increases activity introduction of CH 3 Although they exhibited less anti-HIV-1 activity compared to standard drug zidovudine (half-maximal inhibitory concentration IC 50 = 0.016 µM), these compounds showed significant anti-HIV-1 activity at micromolar concentrations (IC 50 within the range of 7.50-20.83 µM) ( Table 1). The introduction of electron-withdrawing groups, such as fluorine or trifluoromethyl on phenyl ring (derivatives 8 and 9), enhanced antiviral activity compared to the unsubstituted phenyl derivative 7.…”
Section: -10mentioning
confidence: 99%
“…It has been observed that the 2-amino-1,3,4-thiadiazole moiety may be a good group for anti-HIV-1 activity by providing promising antiviral agents. (7) substitution with F atoms (8,9) Molecular modeling studies for the pyrimidyl derivative 10 showed the formation of two potential intermolecular hydrogen bonds involving a nitrogen atom and the amino group of the thiadiazole ring and aminoacids from NNBS of RT. The introduction of electron-withdrawing groups, such as fluorine or trifluoromethyl on phenyl ring (derivatives 8 and 9), enhanced antiviral activity compared to the unsubstituted phenyl derivative 7.…”
Section: -10mentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrogen-containing heterocycles are found in a wide range of natural products and biologically active synthetic compounds (8)(9)(10)(11)(12)(13)(14)(15). In addition, nitrogen-containing heterocycles constitute a common structural unit of many marketed drugs (16,17).…”
Section: Pharmaceutical Chemistry Department Faculty Of Medicine Andmentioning
confidence: 99%
“…Lactic acid exists naturally in two optical isomers: d(-)-lactic acid and l(+)-lactic acid. Since elevated levels of the disomer are harmful to humans, l(+)-lactic acid is the preferred isomer for food-related and pharmaceutical industries [3,4]. It is the simplest 2-hydroxycarboxylic acid with a chiral atom and exists oin two enantiomeric firms (Fig.1).…”
mentioning
confidence: 99%